Dose the say on pay law decelerate CEOs compensation growth in the UK？ - Wu, Miao (2019)
In this paper, the main research question is that the say on pay law decelerates CEOs compensation growth in the UK. In order to clearly show the results of fair, in this paper, the research model which was determined by the agency theory is a CEO pay and company performance relationship. Hypothesis development were determined through management power theory and stewardship theory. In order to get the conclusion, it examines three hypotheses by analyzing four time period of eight - year data, which are salary, shares, option, pension, total compensation, Long-term incentive plan and net income from 100 companies listed on the London stock exchange. Then, it concluded that after the promulgation of say on pay law, the sensitivity of CEO compensation of weak corporate governance to the performance of the company is better. At the same time, this paper refutes management theory that the CEO encroaches aches on the company's benefits and quality his own salary and confirmed say on pay law do reduce CEO pay and the growth of CEO pay. Finally, after the modification of say on pay law in 2013, say on pay law had no significant impact on the company's total CEO compensation.